Screening for domestic violence in Jordan: validation of an Arabic version of a domestic violence against women questionnaire - Linda G Haddad; Ali Shotar; Janet B Younger; et al (Dove Medical Press, 2011)
Linda G Haddad1, Ali Shotar2, Janet B Younger1, Sukaina Alzyoud3, Claudia M Bouhaidar11Virginia Commonwealth University School of Nursing, Richmond, VA, USA; 2Forensic and Legal Medicine Department, Jordan University of Science and Technology, Irbid, Jordan; 3Hashemite University School of Nursing, Zarqua, JordanObjectives: Abuse against women causes a great deal of suffering for the victims and is a major public health problem. Measuring lifetime abuse is a complicated task; the various methods that are used to measure abuse can cause wide variations in the reported occurrences of abuse. Furthermore, the estimated prevalence of abuse also depends on how abuse is culturally defined. Researchers currently lack a validated Arabic language instrument that is also culturally tailored to Arab and Middle Eastern populations. Therefore, it is important to develop and evaluate psychometric properties of an Arabic language version of the newly developed NorVold Domestic Abuse Questionnaire (NORAQ).Design and methods: The five core elements of the NORAQ (emotional abuse, physical abuse, sexual abuse, current suffering of the abuse, and communication of the history of abuse to the general practitioner) were translated into Arabic, translated back into English, and pilot tested to ensure cultural sensitivity and appropriateness for adult women in the Eastern Mediterranean region. Participants were recruited from the Jordanian Ministry of Health-Maternal and Child Health Care Centers in two large cities in Jordan.Results: A self administered NORAQ was completed by 175 women who had attended the centers. The order of factors was almost identical to the original English and Swedish languages questionnaire constructs. The forced 3-factor solution explained 64.25% of the variance in the measure. The alpha reliability coefficients were 0.75 for the total scale and ranged from 0.75 to 0.77 for the subscales. In terms of the prevalence of lifetime abuse, 39% of women reported emotional abuse, 30% physical abuse, and 6% sexual abuse.Conclusion: The Arabic version of the NORAQ has demonstrated initial reliability and validity. It is a cost-effective means for screening incidence and prevalence of lifetime domestic abuse against women in Jordan, and it may be applicable to other Middle East countries.Keywords: domestic violence, Middle East, Jordan, instrumentation